Fauna parasitaria de Calophysus macropterus (Lichtenstein, 1819) "mota" cultivados en ambientes controlados en la región de San Martín - Gutiérrez Tuanama, Willy (2021)
The objective of this research work was the taxonomic identification of the Calophysus macropterus "mota" parasites and to determine the parasitic indices in fish grown in ponds in the San Martín region. The work was carried out at the Centro de Investigaciones “Carlos Miguel Castañeda Ruiz”, of the Instituto de Investigaciones de la Amazonía Peruana (IIAP) - San Martín Region, between April-October 2017. The fish were extracted weekly with a trawl net to later carry out the respective necropsy in the laboratory. A total of 30 specimens were analyzed by sacrificing them with a stylet at the height of the cephalic region, according to Eiras, 2003. The external and internal organs were separated to be observed in search of parasites, which were placed separately on microscope slides to be identified, according to taxonomic keys of Thatcher 2006. The parasitic fauna consisted of monogeneous parasites of the genus Demidospermus, located at the level of the fish gills, nematode larvae L3 belonging to the Anisakidae family were also found in the mesentery of the fish under study. Parasitic indices of the genus Demidospermus presented a prevalence of 10%, average intensity of 5 parasites per fish and nematode larvae L3 had a prevalence of 13.33% and average intensity of 21.5 parasites per fish. It is concluded that the monogenea of the genus Demidospermus and nematode larvae of the Anisakidae family showed low parasitic indices in Calophysus macropterus in culture ponds.